Circulatory miR-98-5p levels are deregulated during diabetes and it inhibits proliferation and promotes apoptosis by targeting PPP1R15B in keratinocytes - Khan, Rukshar (RNA Biol, 2019)
Although deregulated circulatory miRNA signatures during diabetes have been identified for some years now, the effects of such miRNAs on several target tissues are not yet thoroughly investigated. The skin that is nourished by components present in the circulation exhibits several notable abnormal features during diabetes. We, therefore, hypothesized that such altered circulatory miRNA levels might be critical in the onset and progression of impaired skin health during diabetes. RNA sequencing from blood samples of normal and type 2 diabetic human subjects identified 9 upregulated and 19 downregulated miRNAs. miR-98-5p was significantly downregulated and its overexpression down-regulated PPP1R15B levels in HaCaT cells and this was prevented by the miR-98-5p inhibitor. This was validated in human primary epidermal keratinocytes and further supported by a dual reporter luciferase assay of the PPP1R15B 3ʹUTR where miR-98-5p significantly decreased the luciferase activity which was prevented in the presence of the miRNA inhibitor and by mutation in the miRNA binding site. By targeting PPP1R15B, miR-98-5p increases levels of p-eIF2α, BiP and CHOP. Consequently, there was induction of apoptosis accompanied with decreased proliferation in the presence of miR-98-5p. Conversely, miR-98-5p inhibition alone inhibited apoptosis and promoted proliferation. Taken together, our data suggest that by targeting PPP1R15B, miR-98-5p induces apoptosis and decreases proliferation. As opposed to this since circulatory miR-98-5p levels are decreased in diabetes, we believe that this decrease in the circulation that feeds the skin layers might be a major contributor of hyperproliferation as seen in the skin during diabetes. Abbreviations: miRNAs: MicroRNAs; PPP1R15B: PPP1R15B: Protein Phosphatase 1 Regulatory Subunit 15B; TGFβR1: Transforming Growth Factor Beta Receptor 1; ER: Endoplasmic Reticulum; Bip: Binding Immunoglobulin Protein; Chop: CCAAT-enhancer-binding protein homologous protein; p-eIF2α: Eukaryotic Translation Initiation Factor 2a; Bax: Bcl2-associated X protein; Bcl-2: B-cell CLL/lymphoma 2; PCNA: Proliferating Cell Nuclear Antigen; K5: Cytokeratin 5; qRT-PCR: Quantitative Real-Time PCR; ESCC: Oesophageal squamous cell carcinoma; HCC: Hepatocellular carcinoma; CTHRC1: Collagen triple helix repeat containing 1; SALL4: Sal-like protein 4; TNFα: Tumour Necrosis Factor alpha; PGC-1β: Peroxisome Profilerator-activated receptor-γ coactivator-1β; IGF2BP1: Insulin-like growth factor 2 mRNA binding protein 1.